2011
DOI: 10.1007/s12892-010-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

QTL identification of yield-related traits and their association with flowering and maturity in soybean

Abstract: Two soybean recombinant inbred line populations, Jinpumkong 2 x SS2-2 (J x S) and Iksannamulkong x SS2-2 (I x S) showed population-specific quantitative trait loci (QTLs) for days to flowering (DF) and days to maturity (DM) and these were closely correlated within population. In the present study, we identified QTLs for six yield-related traits with simple sequence repeat markers, and biological correlations between flowering traits and yield-related traits. The yield-related traits included plant height (PH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 33 publications
6
59
0
Order By: Relevance
“…Other studies in biparental populations reported additional QTL related to pod number under field conditions (i.e. Hu et al, ; Liu et al, ; Shim, Kim, Ha, Lee, & Lee, 2017; Zhang et al, ), however, distributed throughout the whole genome and none of them close to the QTL identified here. A GWAS study by Fang et al () failed to detect SNP marker that were significantly associated with total pod number.…”
Section: Discussionmentioning
confidence: 39%
“…Other studies in biparental populations reported additional QTL related to pod number under field conditions (i.e. Hu et al, ; Liu et al, ; Shim, Kim, Ha, Lee, & Lee, 2017; Zhang et al, ), however, distributed throughout the whole genome and none of them close to the QTL identified here. A GWAS study by Fang et al () failed to detect SNP marker that were significantly associated with total pod number.…”
Section: Discussionmentioning
confidence: 39%
“…The number of identified quantitative trait loci (QTLs) for NPS-related traits continues to increase. More than 60 QTLs of NPS-related traits have been identified in soybean (Fernando et al, 2014;Guo et al, 2011;Huang, Zhao, Yu, Chen, & Gai, 2009;Josiane et al, 2016;Liu et al, 2015;Liu et al, 2011Liu et al, , 2017Niu et al, 2013;Sun et al, 2006;Wang, Zhang, Zhou, & Sha, 2007;Yang et al, 2013;Zhang et al, 2010;Zhou et al, 2005). However, only a few were repeatedly detected in different years and even fewer verified QTLs were identified in different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen molecular markers also presented association with more than one trait. QTL for the respective trait in the same linkage groups have been reported (Reinprecht et al 2006, Gai et al 2007, Zhang et al 2010, Liu et al 2011, Kim et al 2012. Other QTL related to these traits can also be found in the Glicyne max (http://soybase.org/) genomic database.…”
Section: Jis Rodrigues Et Almentioning
confidence: 68%
“…QTL are reported for traits related to weight and size of the seeds (Liu et al 2011, Xu et al 2011, Han et al 2012, Sun et al 2012, Hu et al 2013, Liu et al 2013, Pathan et al 2013, Yesudas et al 2013, Kato et al 2014. Moreover, at least six QTL have been reported for grain yield, specifically (Palomeque et al 2009, Sebastian et al 2010, Kim et al 2012, Fox et al 2015, besides the several QTL mapped for other grain yield components from different populations , Guzman et al 2007, Zhang et al 2010, Liu et al 2011, Liu et al 2013.…”
Section: Jis Rodrigues Et Almentioning
confidence: 99%
See 1 more Smart Citation